Sikap Positif Bahasa Indonesia Sebagai Jati Diri Bangsa - Alifia Fitriyanti; Amelia Listianti Putri (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
In Law Number 24 of 2009 Article 25 it is stated that the Indonesian language is a national identity, national pride, a means of unity as an ethnic group, as well as a means of communication between regions and between regional cultures. Therefore, as an Indonesian language user, you should be proud to use Indonesian. However, in the context of higher education, most students do not really have a positive linguistic attitude. Awareness of feeling loyal, proud to own, and maintain the Indonesian language seems to be lacking. This is because students tend to be more confident when using a foreign language compared to their own country's language. A positive attitude in Indonesian can be shown in the form of language loyalty, language pride, and awareness of language norms.